Analysis of the History and Development of Islamic Economic Thought in the Ottoman Turkey (1299–1922 CE) - Suci Septiani; Nurhikmah Nurhikmah; Idris Parakkasi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to explore the intellectual and institutional contributions of the Ottoman Caliphate to the development of modern Islamic economics. Using a qualitative historical approach and library research, the study analyzes key Ottoman economic institutions, such as productive waqf (cash waqf), hisbah, timar, iltizam, as well as the scholarly thoughts of Ottoman ulama on ethics and economic regulation. The findings indicate that the Ottoman cash waqf served as a foundation for modern Sharia financial innovations, including waqf-based microfinance and sukuk, while hisbah and fiscal regulations provided early models for market governance and Sharia- based public finance. The intellectual contributions of Ottoman scholars emphasized the integration of justice, trust (amanah), and social welfare in economic practice, inspiring contemporary Islamic business ethics and Sharia governance. This study concludes that the Ottoman intellectual and institutional legacy is not only historically significant but also provides strategic references for developing a just, inclusive, and sustainable modern Islamic economy.